Seroprevalence of Toxoplasma gondii and Associated Risk Factors in Pregnant Women in Araçatuba, São Paulo, Brazil: A Multi-Level Analysis - Tatiani da Silva Palhota Lozano; Aline Benitez; Joice Cristina dos Santos; Italmar Teodorico Navarro; Walter Bertequini Nagata; Michel dos Santos Pinto; Jancarlo Ferreira Gomes; Gabriele Zaine Teixeira Debortoli; Thaís Rabelo Santos-Doni; Katia Denise Saraiva Bresciani (Microorganisms)
This study assessed the seroprevalence of Toxoplasma gondii and risk factors among 428 pregnant women attending Basic Health Units (BHUs) in Araçatuba, São Paulo, Brazil. The seroprevalence was 55.14%, indicating high exposure to the parasite in this population. Using a multi-level logistic regression model, this study analyzed these predictors to determine their association with a higher seropositivity rate, with BHUs included as a random factor. Predictors associated with higher seropositivity included older age (36–45 years), with a 71.64% prevalence in this group, and multiparity (61.65%). Women with lower educational levels were also more likely to be infected, with 59.46% seropositivity recorded among those who had only completed elementary school. Despite identifying several risk factors, no significant correlation was found between undercooked meat consumption or contact with soil and infection. These findings highlight the need for targeted public health interventions, particularly for educating high-risk groups about toxoplasmosis prevention, such as safe food handling and avoiding raw dairy products. Additionally, BHUs play a critical role in early detection and prevention. These units are important for providing healthcare access and preventive education for vulnerable populations. Given the high seroprevalence, this study underscores the urgency of implementing prenatal screening and educational programs to reduce the risks of congenital toxoplasmosis in this region.